In larger freedom : towards development, security and human rights for all (UN New YorkUS, 2005)
Reports on the implementation of the Millennium Declaration in the areas of peace, security, disarmament, human rights, democracy and good governance.
Keywords: ECONOMIC DEVELOPMENT